1992
DOI: 10.1042/bj2830473
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of a theory of molecular recognition using human insulin-like-growth-factor-I fragment 21–40 and its complementary peptide

Abstract: Using solid-phase methods we have synthesized human insulin-like-growth-factor-I (IGF-I) fragment 21-40 (IGF-I 21-40) and the peptide derived from the 5'----3' translation of the complementary nucleic acid of this peptide, 'I-FGI 20-40' (the complementary peptide). According to a recently proposed theory of molecular recognition, these two peptides should bind specifically to each other. We have tested this theory by using both solid- and solution-phase direct-binding assays for this complementary-peptide pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Sometimes, the complementary strand may have a stop codon. Besides the universality of the theory is still controversial [28].…”
Section: Novel Methods For Prediction Of Interaction Sitesmentioning
confidence: 99%
“…Sometimes, the complementary strand may have a stop codon. Besides the universality of the theory is still controversial [28].…”
Section: Novel Methods For Prediction Of Interaction Sitesmentioning
confidence: 99%
“…Numbers in brackets following each sequence refer to its location within the sequence of rbGH. Peptides were synthesised by standard solid-phase fluorenylmethoxycarbonyl chemistry [17] and analysed by reverse-phase HPLC as described previously [18]. A control peptide (CRSPELETFSC) was synthesied by solid-phase fluorenylmethoxycarbonyl chemistry on an Applied Biosystems 431A automated peptide synthesiser and was analysed as described above.…”
Section: Animalsmentioning
confidence: 99%
“…The same research group later found a similar highaffinity association between the g-endorphin peptide and a synthetic 5' 33' complementary peptide whose sequence had been deduced in the same way. [54] There is, as yet, no clear explanation as to why specific sense/complementary peptide interactions should not be observed reproducibly in these experiments whilst being seen with such apparent ease in others. Some of these applications will be discussed in a little more detail below.…”
Section: Observations With Sense/complementary Peptide Systemsmentioning
confidence: 74%